THE EFFECT OF PRICE AND CELEBRITY ENDORSERS ON PURCHASE DECISIONS WITH BRAND IMAGE AS AN INTERVENING VARIABLE IN MS GLOW SKINCARE PRODUCTS - Endang Satriani Siregar; Paham Ginting; Beby Karina Fawzeea Sembiring (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
Skincare products also support this development. The goal of skincare is to maintain healthy and firm skin through a series of skincare treatments that utilize specific products. Customers who value their appearance will undoubtedly choose skincare products that provide the highest level of happiness when worn, which of course encourages manufacturers to develop more innovative products in an effort to attract customers. MS Glow, a skincare company that has recently joined the Indonesian beauty product industry, managed to bring home the Indonesia Best Brand Award 2020 in the field of Exclusive Facial Care. This type of research uses a quantitative approach and is associative in nature. This research was conducted in Rantauprapat City, Labuhanbatu Regency, North Sumatra Province, aimed at customers who use MS Glow Skincare products and the research time was carried out starting from September-December 2024. The population of this study includes MS Glow customers.